(untitled) (Journal of Applied Oral Science, 2016)
Orthodontic treatment with fixed brackets plays a major role on the formation of white spot lesions. Objective This study aimed to incorporate silver nanoparticle solutions (AgNP) in an orthodontic adhesive and evaluate its physicochemical and antimicrobial properties. Material and Methods Silver nanoparticle solutions were added to a commercial adhesive in different concentrations (w/w): 0%, 0.11%, 0.18%, and 0.33%. Shear bond strength (SBS) test was performed after bonding metal brackets to enamel. Raman spectroscopy was used to analyze in situ the degree of conversion (DC) of the adhesive layer. The surface free energy (SFE) was evaluated after the measurement of contact angles. Growth inhibition of Streptococcus mutans in liquid and solid media was determined by colony-forming unit count and inhibition halo, respectively. One-way ANOVA was performed for SBS, DC, SFE, and growth inhibition. Results The incorporation of AgNP solution decreased the SBS (p